Bark beetles in Chile: a review of the current situation and its effects in the international trade - Ruiz G., Cecilia; Lanfranco L., Dolly (Bosque (Valdivia), 2008)
One of the main Chilean forestry exported products, and also showing better development prospects, is the saw wood of Pinus radiata; this is due to high levels of future availability of good quality logs to supply its industry and the growing global demand for this product. However, these exports have been affected by the presence, in the country, of three bark beetles introduced species: Hylurgus ligniperda, Hylastes ater and Orthotomicus erosus (Coleoptera: Scolytidae). As these insects are considered quarantine pests to major markets importing Chilean products, particularly saw wood, its presence in shipments from Chile could restrict the marketing of these products, thus producing a great impact on the regional and national economy. In 2006, the Servicio Agrícola y Ganadero (SAG) and private managers associated to the Corporación Chilena de la Madera (CORMA) suspended the green sawed wooden exports to Mexico, owing to the presence of adults of H. ligniperda in some shipments, what generated both from the point of view of the State and from the exporters as well, the implementation of some measures to correct these effects in the commercialization of these products. Some biological and ecological bark beetle aspects, its role transporting fungal spores of sapstains and pathogens, as well as its importance as quarantine pests feasible to be introduced into the main markets were analyzed and discussed. Some measures adopted by the government and the forestry sector to get to external markets with minimum risk of pests are also presented.